Understanding COVID-19 vaccine hesitancy and resistance: another challenge in cancer patients - Mejri, Nesrine; Berrazega, Yosra; Ouertani, Emna; Rachdi, Haifa; Bohli, Mariem; Kochbati, Lotfi; Boussen, Hamouda (Supportive care in cancer, 2022)
Introduction We aimed to measure the acceptability towards the COVID-19 vaccination in cancer patients and to investigate determinant factors associated with the patient’s choice. Methods We conducted a cross-sectional survey with a self-administered questionnaire delivered to 329 cancer patients in 3 oncology cancer centers in Tunisia between February-May 2021. Logistic regression was used to evaluate odds ratio predicting patient’s intentions toward the vaccine. Results Acceptance rate was 50.5%, 28.3% ( n = 93) reported to definitely refuse the vaccine and 21.2% ( n = 70) did not make their decision yet. High educational level, history of comorbidities, history of influenza vaccination in the current season, and patient’s opinion about the severity of COVID-19 did not predict vaccine resistance. However, patients who think that the vaccine may interfere with treatment efficacy (OR = 7.28, 95%CI [2.5–12.32]), or may impact cancer outcome (OR = 6.14, 95%CI [2.27–16.7]), were significantly more likely to refuse the vaccine. Patients who disagree that the vaccine is a major weapon against the pandemic (OR = 6.07, 95%CI [2.34–9.52]) or that it could reduce the virus transmission (OR = 7.34, 95%CI [4.22–11.81]) were also significantly more likely to reject the vaccination. Safety concerns were also significant predictive factors (OR = 7.9, 95%CI [4.10–11.27]. Confidence level in the authorities played a significant role in patient’s acceptance of the vaccine, indeed patients who are not registered (OR = 5.9, 95%CI [1.58–8.7]) or not informed about the Tunisian national vaccination platform EVAX (OR = 5.51, 95%CI [2.1–7.9]) were more likely to be against the vaccine. Conclusion Cancer patient’s education about the impact of the vaccine on their disease and on the COVID-19 is needed. Governments should build strategies to gain more population confidence.